Museus e Patrimônio: Pensamento Cibertecnológico e Cultura Digital - SILVA, Carmen Lucia Souza da (Universidade de Brasília, 2023)
In this work, we present a reflection on how digital technologies have changed the way we experience museums and cultural heritage in the last decades and even in a context of social isolation motivated by the Covid-19 pandemic. We revisit the ideas and thoughts of theorists such as Wiener, Haraway, Pre ciado and Levy to reflect, from cybernetics to cyborg and datacentric culture, on these transformations when considering the sub ject-technology-society interrelationship. For that we also point out formative or historical landmarks, in Brazil and in the world, which culminate in a range of resources that expand memories and museological spaces with the impulse of cyber technologies. Advents that are at the base of what is called digital cul ture, where society is remodeled, affected by technological addenda. We also bring results from cartographies of spaces on the internet of Brazilian museum institutions, carried out between 2018 and 2020, which signal how we are in an immersion process in digital culture.